Analisis Nilai-Nilai Permainan Tradisional Gobak Sodor dengan Teori Pengambilan Keputusan Karier Krumboltz - Hidayah, Karisma Khoirul (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2022)
This study aims to analyze the values ??in the traditional game of gobak sodor with krumboltz career decision-making theory. This type of research is library research, namely the study of theoretical and other studies related to values, culture, and norms. The results showed that the values ??of the traditional game of gobak sodor can be applied in making krumboltz career decisions. Keywords: gobak sodor, Krumboltz . career theory